2014
DOI: 10.1080/19443994.2014.922286
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of porous pavement effectiveness on runoff reduction under climate change scenarios

Abstract: A B S T R A C TClimate change has affected both water quantity and quality by increased rainfall, runoff, and associated pollutant loading in urban areas. Stormwater Best Management Practices (BMPs) are now being popularly considered for the reduction of increased runoff due to urbanization. Most research has been conducted on the analysis of BMP effectiveness under current conditions. However, there is no extensive literature on BMP effectiveness studies considering climate change. In this study, the effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 12 publications
(9 reference statements)
0
15
0
Order By: Relevance
“…These authors found that the concentration of suspended solids and heavy metals are reduced by at least 50% when stormwater filters through permeable pavement. With regard to hydraulic performance, Abbott and Comino-Mateos (2003), Collins et al (2008), Fassman and Blackbourn (2010), Pratt et al (1989;1995), TRCA (2008), Huang et al (2012), Drake et al (2012;2014a) and Kim et al (2015) all showed, for various individual cases, that permeable pavement helps reduce peak flow rate and runoff volume in the storm sewer system during rainfall events. Among these authors, only Drake et al (2014a), Drake et al (2012), Huang et al (2012) and TRCA (2008) demonstrated these effects in a harsh winter climate, with winter thaws, such as those occurring in southern parts of Canada.…”
Section: Introductionmentioning
confidence: 99%
“…These authors found that the concentration of suspended solids and heavy metals are reduced by at least 50% when stormwater filters through permeable pavement. With regard to hydraulic performance, Abbott and Comino-Mateos (2003), Collins et al (2008), Fassman and Blackbourn (2010), Pratt et al (1989;1995), TRCA (2008), Huang et al (2012), Drake et al (2012;2014a) and Kim et al (2015) all showed, for various individual cases, that permeable pavement helps reduce peak flow rate and runoff volume in the storm sewer system during rainfall events. Among these authors, only Drake et al (2014a), Drake et al (2012), Huang et al (2012) and TRCA (2008) demonstrated these effects in a harsh winter climate, with winter thaws, such as those occurring in southern parts of Canada.…”
Section: Introductionmentioning
confidence: 99%
“…In the pervious area, there was no runoff at all for the first 7 to 12 minutes of the storm, as the depression storage and available infiltration capacity were sufficient to capture all rainfall volume during this period. The expected findings are supported by Kim et al (2015) and Barszcz (2015), where peak flow and total runoff volume after permeable pavement controlled are smaller than the values of the existing condition with AP, indicating that pervious pavement has infiltrated most of the runoff into groundwater. Overall, the runoff hydrograph for 15 min 100-yr storm was the largest.…”
Section: Hydrological Assessmentmentioning
confidence: 67%
“…Permeable pavements have been widely used since 1982 in the USA and in the 1990s in Canada, Europe and Japan as a measure to control stormwater (Mosquera and Drake, 1998; Pratt, 1999; Dietz, 2007; O’Sullivan et al ., 2011). Permeable pavements have been extremely effective in infiltrating stormwater runoff (Watanabe, 1995; Fach and Geiger, 2005; Zhou and Li, 2008; Bastien et al ., 2011; Sañudo‐Fontaneda et al , 2013; Barszcz, 2015), significantly reducing runoff volume (Pratt et al ., 1989; Davey and Maziliauskas, 2003; Lin et al ., 2014; Timm et al ., 2018) and minimising peak flow (Price, 1994; Kim et al ., 2015; Imteaz et al ., 2018; Su et al ., 2019). Permeable pavements that commonly used are pervious concrete (PC), porous asphalt (PA) and permeable pavers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Hydrologic designs computation of rainfall extremes is important for both structural as well as non-structural flood protection measures [9]. SWMM is the open source software tool which is available most widely for research activities and solving real problems of Urban Floods in an urbanized catchment [10]. From this we can easily incorporate modeling capabilities for both hydraulic and hydrologic conditions which is its major advantage over other Applicability of SWMM for semi Urban Catchment Flood modeling using extreme Rainfall Events available tools.…”
Section: Introductionmentioning
confidence: 99%